Manganese Oxide Based Core@Shell Nanoparticles and Its Application in Aqueous Zinc-Ion Battery (Journal of Engineering Science, 2024)
In this study, MnO2 as well as core@shell type MnO2@Ag material were prepared through the versatile reverse micelle route. FTIR absorption band at 522 cm-1 was ascribed to the Mn-O stretching mode, demonstrating the presence of a Mn-O bond inside the MnO2 structure. XRD was used to determine the crystalline structure of the prepared samples. Peaks at 2θ = 12.7°, 18.1°, 28.8°, 37.5°, 42.1°, 49.9°, 56.2°, and 60.3° matched the α-MnO2 diffraction peaks nicely. The spherical shape of the produced MnO2 and MnO2@Ag compounds was observed in FESEM. The results of the histogram show that MnO2@Ag particles are marginally smaller than MnO2 particles. The electrochemical assessment of the generated cathode materials for aqueous zinc-ion battery (AZIB) CR-2032 was conducted using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and battery charge-discharge (BCD) techniques.Journal of Engineering Science 14(2), 2023, 69-77